2015
DOI: 10.3402/pba.v5.25796
|View full text |Cite
|
Sign up to set email alerts
|

LINGO-1 promotes lysosomal degradation of amyloid-β protein precursor

Abstract: Sequential proteolytic cleavages of amyloid-β protein precursor (AβPP) by β-secretase and γ-secretase generate amyloid β (Aβ) peptides, which are thought to contribute to Alzheimer's disease (AD). Much of this processing occurs in endosomes following endocytosis of AβPP from the plasma membrane. However, this pathogenic mode of processing AβPP may occur in competition with lysosomal degradation of AβPP, a common fate of membrane proteins trafficking through the endosomal system. Following up on published repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Complex formation with LRP, BACE1 and Ran-binding protein 9 (RanBP9), a scaffolding protein involved in trafficking of membrane receptors [240] , reduces APP cell surface localization, and favors internalization of APP and generate Aβ [241, 242] . Similar functional outcome has been proposed for the interaction of APP with lingo proteins [151, 243] , which can form a complex with NgR and p75 [244, 245] . Lingo family of proteins has been associated with growth factor receptor internalization and subsequent proteasomal degradation in other systems [245, 246] .…”
Section: Functional Consequence Of App Internalization On Aβ Clearancesupporting
confidence: 64%
See 1 more Smart Citation
“…Complex formation with LRP, BACE1 and Ran-binding protein 9 (RanBP9), a scaffolding protein involved in trafficking of membrane receptors [240] , reduces APP cell surface localization, and favors internalization of APP and generate Aβ [241, 242] . Similar functional outcome has been proposed for the interaction of APP with lingo proteins [151, 243] , which can form a complex with NgR and p75 [244, 245] . Lingo family of proteins has been associated with growth factor receptor internalization and subsequent proteasomal degradation in other systems [245, 246] .…”
Section: Functional Consequence Of App Internalization On Aβ Clearancesupporting
confidence: 64%
“…Knockdown of lingo expression reduces Aβ production, apparently by favoring α-secretase processing of APP. However, overexpression of lingo results in increased lysosomal degradation of APP [243] .…”
Section: Functional Consequence Of App Internalization On Aβ Clearancementioning
confidence: 99%
“…It is also shown that expression of LINGO-1 was down-regulated in AD cortical gray matter [160]. Over-expression of LINGO-1 in cortical neurons significantly reduced APP levels, which supports the hypothesis that LINGO-1 promotes APP degradation and inhibits Aβ generation [159].…”
Section: Endo-lysosomal Autophagy Pathway Failurementioning
confidence: 70%
“…LINGO-1 is predominately expressed in the central nervous system [202]. Experimental reports demonstrated that the physical interaction between LINGO-1 and APP promotes lysosomal degradation of APP, and thereby reduces available APP for amyloidogenic process [159]. It is also shown that expression of LINGO-1 was down-regulated in AD cortical gray matter [160].…”
Section: Endo-lysosomal Autophagy Pathway Failurementioning
confidence: 99%
“…Receptor tyrosine kinases negatively regulated by LINGO-1 include TrkA, TrkB and TrkC (present results and Fu et al, 2010) and EGFR/ErbB1 (Inoue et al, 2007). Receptor tyrosine kinases are not the only cellular targets of LIG protein-mediated regulation, however, as a C. elegans LRIG ortholog positively regulates signaling by BMP receptors (Gumienny et al 2010) and LINGO-1 enables signaling by NgR/p75 NTR complexes (Mi et al, 2004) and promotes lysosomal degradation of the β-amyloid precursor protein (de Laat et al, 2015). …”
Section: Discussionmentioning
confidence: 99%